Risk assessment on clinical waste activity for a selected dialysis activity / Farid Hakem Nozlan - Farid Hakem, Nozlan (2022)
Clinical waste management is the main activities during the dialysis activities. The activity has been considered as risky activity it because involving the human health. The purpose of research is to create a safer of workplace for dialysis workers during clinical waste activity at dialysis center. The main objective of the research is to identify potential hazard that occur during the dialysis activity, to determine the hazard and access the control measure to reduce the risk and hazard at dialysis center. The methodology that been applied in the research which is site observations at selected dialysis center at Selangor to identify the potential hazard. Questionnaire been constructed thru the survey and 60 respondents were involve identifying the hazard among dialysis center workers. The HIRARC form is used to identify the risk assessment and risk control after the process identification hazard during the survey. The research finds there were potential hazard occur in clinical waste during dialysis activity which is physical. Biological ,chemical and ergonomic hazard. The analysis from the survey shows that the workers at dialysis center are aware of the exposed to the hazard. Majority of the respondent were strongly agreed that by improve the risk control could reduce the hazard exposure. In the summary of HIRARC assessment found that there were 3 high risk hazard form 19 hazard that need immediate action and control measure to reduce the risk that will give impact to the workers. In this research, risk control was suggested to reduce the risk and to improve the lack of implementation of the control measure. It can be concluded that there was hazard occur in clinical waste activity during dialysis activity and most of them were low and medium risk. Without comprehensive action taken by employer, the hazard can give impact to human and environment.